2014
DOI: 10.1111/gove.12129
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Rule and Varieties of Governance

Abstract: This article reexamines the venerable concept of indirect rule. We argue, drawing on evidence from colonial and postcolonial South Asia, that indirect rule actually represented a diverse set of governance forms that need to be clearly distinguished. Using a new typology of varieties of governance, we show that colonial governments established suzerain, hybrid, and de jure governance, in addition to direct rule across territories, based on the incentives and constraints of the state. The repertoire of governanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Naseemullah and Staniland, 2014). This study contributes to the growing evidence in South Asia that these forms of rule can both successfully adapt to contextual shifts and prove resilient to external interventions.…”
Section: Discussionmentioning
confidence: 80%
“…Naseemullah and Staniland, 2014). This study contributes to the growing evidence in South Asia that these forms of rule can both successfully adapt to contextual shifts and prove resilient to external interventions.…”
Section: Discussionmentioning
confidence: 80%
“…This devolution of power can be explained by limited resources, poor policy planning, and a rapidly increasing population resulting from rural to urban migration and displacement caused by conflict. Some have suggested that this hands-off approach to governance is a post-colonial legacy of indirect rule 34 and (or) a continuity of the criminal-cum-political strongmen of British India who worked as intermediaries between the rulers and the ruled. 35 As in many regions of the world, historical legacies shape both political developments and the nature of crime.…”
Section: Resultsmentioning
confidence: 99%
“…Naseemullah and Staniland (2014) note that state governance is highly uneven in post-colonial settings, often utilizing forms of indirect rule via informal and non-state actors.…”
Section: Hybrid Political Ordersmentioning
confidence: 99%